2015
DOI: 10.1016/j.bpj.2014.11.1858
|View full text |Cite
|
Sign up to set email alerts
|

NMR-Detected Brownian Dynamics of α B-Crystallin over a Wide Range of Concentrations

Abstract: Knowledge about the global translational and rotational motion of proteins under crowded conditions is highly relevant for understanding the function of proteins in vivo. This holds in particular for human αB-crystallin, which is strongly crowded in vivo and inter alia responsible for preventing cataracts. Quantitative information on translational and rotational diffusion is not readily available, and we here demonstrate an approach that combines pulsed-field-gradient NMR for translational diffusion and proton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 53 publications
3
42
0
Order By: Relevance
“…Interparticle interactions can affect to different extents the translational and the rotational diffusion. On this topic, the reader is referred to the discussion given by Krushelnitsky in [76] and by Roos et al in [136].…”
Section: Resolution and Sensitivity Of Sedimented Proteinsmentioning
confidence: 97%
“…Interparticle interactions can affect to different extents the translational and the rotational diffusion. On this topic, the reader is referred to the discussion given by Krushelnitsky in [76] and by Roos et al in [136].…”
Section: Resolution and Sensitivity Of Sedimented Proteinsmentioning
confidence: 97%
“…At very high concentrations globular proteins typically retain a high degree of rotational mobility as they can rotate rather freely within a cage. It is found that the correlation time of rotational diffusion τ R is proportional to the molecular weight M W following the relation τ R (µs) ~ M W 3/d (kDa), with d being approximately d=2.5 [53]. Depending on temperature, a rotational correlation time τ R on the order of 1.2-5.7 µs was found for αB-crystallin [9,53].…”
Section: Sedimentation Fails To Explain the Intensities Of Differentimentioning
confidence: 98%
“…Molecular crowding impacts both translational and rotational diffusion of a protein. Whereas translational diffusion is largely determined by viscosity, intermolecular protein-protein interactions have a much smaller effect on rotational diffusion [53]. At very high concentrations globular proteins typically retain a high degree of rotational mobility as they can rotate rather freely within a cage.…”
Section: Sedimentation Fails To Explain the Intensities Of Differentimentioning
confidence: 99%
“…Provided that only the viscosity depends on the concentration c of the dispersed particles but not the particle's (apparent) hydrodynamic size, long-time translational diffusion coefficients may thus be expected to follow the same concentration dependence as the inverse viscosity of the same solution. 24,29 For proteins under macromolecular crowding the applicability of the GSE relationship is either confirmed 10,30,31 or shown to be invalid, 31,32 depending on the specific proteins and crowding agents used. 28 However, for charge-stabilized colloids deviations have been noticed.…”
Section: Introductionmentioning
confidence: 99%